Boltysh astrobleme (impact structure): Where? When? As? - Dykan, K.V.; Дикань, Н.І. (Reports of the National Academy of Sciences of Ukraine, 2020)
For the first time, numerous remains of fossil ostracods (genera Cytherella, Cypridea, Clithrocytheridea, Mongolianella, Rhinocypris, Bairdopillata, Schuleridea, Polycope, Langtonia, Macronotella) are found in sediments of the Boltysh impact structure (Ukraine).The time of the Boltysh impact event (at the end late Maastrichtian or at the beginning of the early Paleocene), the age of the lower part of sediments of the Boltysh impact structure that formed at the beginning of the Boltysh Crater formation (int. 463–415 m) and the time of formation of the water basin (early Paleocene), reconstruction of physical and geographical conditions of the early Boltysh reservoir are established by ostracods. Model of the relationship of the Boltysh reservoir with the sea at the beginning of its creation as a “lake on the shore of the ocean” was proposed too. The Boltysh basin was a large deep lake close to the oligotrophic or oligo-mesotrophic type with high specific mineralization of water. Migration of sea ostracods from the Tethys Ocean into the lake in the early Paleocene occurred through a small strait, the water exchange between the lake and the ocean was periodic with varying intensity and duration.